Stress concentration of 3-D surfaces with small undulations: Analytical solution. (1st December 2020) - Cheng, Zhengkun; Zhang, Yi; Sun, Xiaoyu; Wang, Tao; Li, Shengquan
Graphical abstract: Highlights: Analytical framework to generate the SCFs for 3-D shallow surfaces was established. Analytical expressions of SCFs for a series of shallow surface morphologies were derived. The SCFs of surface roughness were analytically predicted and validated by finite element analysis. Abstract: Analytical solutions to the stress concentration factors (SCFs) for 3-D surfaces with small undulations are obtained by a boundary perturbation approach, with consideration of the boundary load ratio. And their applications are shown well to a number of shallow irregularities on surfaces. Moreover, the proposed analytical expression is applied to predict the SCFs of 3-D machined surface topography, which is reconstructed by two dimensional Fourier series. Besides, the prediction results are validated by finite element analysis, comparisons between analytical and numerical results suggest that our analytical solution can be used with assured confidence to calculate the SCFs of 3-D real machined surface topographies.